Peran Instrumen KKPR dalam Pembangunan Kota Berkelanjutan Kawasan Perkotaan Siak Sri Indrapura Kabupaten Siak - Eyka Syahputra; Aras Mulyadi; Zulkarnain Zulkarnain (Jurnal Zona, 2025)
Sustainable city development is one of the strategic agendas in regional and spatial planning, especially in urban areas that have historical value and environmental potential, such as Siak Sri Indrapura. One important instrument in supporting sustainable development is the Suitability of Space Utilization Activities (KKPR), which functions to ensure that space use is in line with spatial planning policies and sustainability principles. This research aims to analyze the role of KKPR in realizing sustainable city development in Siak Sri Indrapura, by emphasizing environmental, social and economic aspects. The approach used is qualitative and quantitative methods, through document analysis, interviews with stakeholders, and field surveys. The study results show that the implementation of KKPR in Siak Sri Indrapura contributes significantly to optimizing space functions, preserving cultural heritage areas, and reducing environmental impacts. However, challenges such as limited spatial data and lack of coordination between sectors need to be overcome to increase the effectiveness of the KKPR. The proposed policy recommendations include strengthening monitoring systems, developing technical capacity, and integrating KKPR with community-based development programs. This study provides scientific and practical contributions in efforts to create a competitive, inclusive and environmentally friendly city